Effect of diet low in omega-6 polyunsaturated fatty acids on the global burden of cardiovascular diseases and future trends: evidence from the Global Burden of Disease 2021 - Mao, Qingsong; Kong, Yuzhe (Frontiers in Medicine, 2025)
This research analyzes the worldwide impact of cardiovascular diseases (CVD) associated with low consumption of omega-6 polyunsaturated fatty acids, utilizing data from the 2021 Global Burden of Disease Study.The study explored the influence of diets deficient in omega-6 polyunsaturated fatty acids on CVD across global, regional, and national levels. It examined variations across different age groups and genders and analyzed the relationship between the disease burden and the Socio-Demographic Index (SDI). Furthermore, it employed an ARIMA model to project the future prevalence of CVD linked to insufficient omega-6 intake until 2050.In 2021, insufficient omega-6 intake was linked to roughly 737.88 thousand deaths and 17.87 million disability-adjusted life years (DALYs) due to CVD, showing a decreasing trend in this health burden throughout the study period. The most significant effects were seen in individuals aged 75 and older, with a higher disease burden noted in males. Forecasts suggest likely declines in disease prevalence in regions with high SDI. On a national level, regions like Russia and various countries in North Africa and the Middle East might experience increasing challenges related to CVD due to low omega-6 intake by 2030 and 2050.These results highlight the critical need for preventive strategies for CVD and stress the importance of managing dietary patterns to mitigate health risks.